The Impact of Fuel Quality on the Performance and Maintenance of the Ship’s Main Engine - Marsudi, Sugeng; Yanti, Dyah Agustin Widhi (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
This study aims to analyze the impact of fuel quality on the performance and maintenance of a ship’s main engine. The background of the research arises from the increasing cases of engine component failures caused by low-quality fuel, particularly related to sulfur content, water contamination, and solid particles. The research applied a quantitative approach through laboratory testing of fuel samples and operational observations of the main engine on a 15,000 DWT cargo vessel. Data collection included viscosity analysis, sulfur content measurement, water contamination testing, and engine maintenance records. The results indicate that fuel with viscosity below the standard (decreasing from 180 cSt at 50°C to 120 cSt) increased the specific fuel oil consumption (SFOC) by 6.8%. High sulfur content (3.2% m/m) accelerated deposit formation on the piston crown and exhaust valve. Moreover, water contamination of 0.6% caused micro-corrosion on the fuel pump plunger and shortened the maintenance interval by 1.5 times compared to the standard. The discussion highlights a direct relationship between fuel quality and maintenance cost: within six months, ships operating with low-quality fuel experienced a 22% increase in maintenance cost compared to those using ISO 8217-compliant fuel. In conclusion, fuel quality is a critical factor in maintaining combustion efficiency, engine performance, and maintenance intervals. The study recommends using fuel that meets international standards and improving fuel quality monitoring systems before usage onboard ships.